Development and structural change in Asia-Pacific : globalising miracles or end of a model? - Andersson, Martin; Gunnarsson, Christer (London ; New York : RoutledgeCurzon, 2003)
A consideration of how the Asia-Pacific economies have developed since the financial crises, the effect of global forces on the national Asian economies and their different development paths as they jointly enter this new phase.
Simultaneously published in the USA and Canada.
Includes bibliographical references and index.
oif 06/11/2015
Loans
Keywords: Structural adjustment (Economic policy); Globalization; East Asia